Analisa Dan Audit Tata Kelola Teknologi Informasi Dengan Cobit 5 Framework P.O.07 Pada Biro Administrasi Umum Universitas Muhammadiyah Palangkaraya - Ika Safitri Windiarti; Fitriani Fitriani; Mita Sari; Agung Prabowo (Anterior Jurnal, 2019)
Information technology governance is an integrated part of organizational management that includes leadership, organizational structure and processes that ensure that information technology is utilized as optimal as possible. An institution similar to UMP, especially in the BAU section, it is time to be managed on an IT-based basis in view of the complexity of the work and for the efficiency and effectiveness of the work of employees working at BAU UMP. The purpose of this study is to determine the condition of IT governance in the UMP BAU for now and analyze IT needs for the next 5-10 years by applying the COBIT 5 Framework method. Based on respondent data, for the next 5-10 years, BAU UM Palangkaraya requires at least 6 staff with educational background in IT or Computer Science for each section of 1 staff member. For further research is to work on subdomains PO.08 and PO 09.